Japanese Encephalitis in Children admitted at Patan Hospital - Shresta, SR; Awale, P; Neupane, S; Adhikari, N; Yadav, BK (Journal of Nepal Paediatric Society, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> This is a hospital based retrospective study, which was done in Pediatric ward of Patan hospital. Study period was one and half year (from Srawan 2063 to 2064 poush).Data were taken from discharge book of Pediatric ward, from the record section of this hospital, and from JE surveillance office, WHO, Kathmandu. All children from 1 month to 14 years ,who were admitted in Pediatric ward with symptoms of Meningitis, Meningoencephalitis and Encephalitis were included in this study and patients more than 14 years of age and symptoms not suggestive of meningitis, meningoencephalitis or encephalitis were excluded from the study. Headache; vomiting and fever were the chief complaints of patients. Two patients died during study period. There were 16 patients with serologically confirmed Japanese encephalitis. Key words: Japanese encephalitis virus (JEV), arthropod borne disease, Acute encephalitis syndrome (AES). doi:10.3126/jnps.v29i1.1595 J. Nepal Paediatr. Soc. Vol.29(1) p.17-21